(Hydro)climatological studies of climate change and variability in Central America - Hidalgo León, Hugo G. (2018)
This is the presentation of Hugo Hidalgo at the CORDEX Central America and South America Training Workshop on Downscaling Techniques, in La Paz, Bolivia, June 25 to 27, 2018.